FAKTOR – FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PERUSAHAAN: PROFITABILITAS SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2012 – 2013) - Lathiefatunnisa Nur Islam; Fuad Fuad (Diponegoro Journal of Accounting, 2015)
This study aimed to analyze the factors that affect the timeliness of financial reporting onmanufacturing companies listed in Indonesia Stock Exchange during 2012-2013. Factors tested in this study is solvency, company size, external ownerships, and profitability as moderating variable. The sample used in this study were 180 manufacturing companies that are consistently listed in the Indonesia Stock Exchange in 2012-2013. The data used in this research is secondary data selected based on purposive sampling method. These factors were then tested using logistic regression analysis with a significant level of 10 %. Results of hypotesis testing in this research showed that the variables used in this study, only extenal ownership variable, profitability in moderating external ownership, and profitability in moderating the size of the company having a significant effect on the timeliness of financial reporting.